Reducing Tantrum Behavior in Autistic Children Using Time Out Techniques - Astari Ranny; Marlina Marlina (Universitas Muhammadiyah Enrekang, 2022)
This research was carried out at the Batu Bara State Special School with the subject of the study, a class II autistic child who had excessive tantrums. The purpose of this study was to determine whether the Time Out technique can be effective in reducing tantrum behavior in children with autism. This study used the Single Subject Research (SSR) method at SLB Negeri Batu Bara Medan with the A-B-A research procedure consisting of a alkaline condition (A1), an intervention condition (B) and a saline condition (A2). The implementation of this research was carried out as many as 17 times observations. In the A1 condition five times with the child's tantrums decreasing at the first meeting 15 times and stable in the last three meetings 13 times. Followed by the intervention condition (B) with 7 meetings where the child's tantrum behavior also decreased, at the first meeting in the intervention condition 10 times, the second 9 times, third and fourth 8 times and stable in the last three meetings 7 times, as for the child's condition on the A2 baseline, namely at the first meeting 7 times, the second 6 times and stable in the last three meetings with 5 tantrums. Based on these data, the Time Out technique has proven successful in reducing tantrum behavior in children with Class II Autism Spectrum Disorder at SLB Negeri Batu Bara Medan. Keywords: Autistic Children; Time Out Technique; Tantrum Behavior